SPECIES DIVERSITY OF THE LARGE CENTIPEDES (Chilopoda: Scolopendromorpha) IN THE MUONG NHE NATURE RESERVE, DIEN BIEN PROVINCE - Le, Xuan Son; Tran, Thi Thanh Binh; Tran, Duc Hung (Tạp chí Khoa học và Công nghệ nhiệt đới, 2025)
This paper introduces the results that study on the diversity of the large centipede Scolopendromorpha in Muong Nhe Nature Reserve (Dien Bien province). The results recorded 10 species belonging to five genera and two families. This result has added eight species to the centipede fauna in this area, bringing the total number of species recorded here to 11 species. Of which two species have been recorded by Vu et al. (2020) are Otostigmus multidens and Otostigmus aculeatus; The species Otostigmus voprosus recorded by Schileyko (2007) was not recorded in this study. For the species recorded, the study also provided basic information about the collected specimens such as coordinates, altitude... their distribution in Vietnam and some remark on species, specimens compared to other studies.